Selective Continuous Positive Airway Pressure Withdrawal With Supplemental Oxygen During Slow-Wave Sleep as a Method of Dissociating Sleep Fragmentation and Intermittent Hypoxemia-Related Sleep Disruption in Obstructive Sleep Apnea - Mullins, Anna E.; Parekh, Ankit; Kam, Korey; Castillo, Bresne; Roberts, Zachary J.; Fakhoury, Ahmad; Valencia, Daphne I.; Schoenholz, Reagan; Tolbert, Thomas M.; Bronstein, Jason Z.; Mooney, Anne M.; Burschtin, Omar E.; et al. (Frontiers in Physiology, 2021)
Obstructive sleep apnea (OSA) is thought to impair memory processing, increase expression of amyloid-β (Aβ) and risk for Alzheimer’s disease (AD). Given evidence that slow wave sleep (SWS) is important in both memory and Aβ metabolism, a better understanding of the mechanisms by which OSA impacts memory and risk for AD can stem from evaluating the role of disruption of SWS specifically and, when such disruption occurs through OSA, from evaluating the individual contributions of sleep fragmentation and intermittent hypoxemia. In this study, we used CPAP withdrawal to recapitulate SWS-specific OSA during polysomnography (PSG), creating conditions of both sleep fragmentation and intermittent hypoxemia in SWS only. During a separate PSG, we created conditions of SWS fragmentation but used oxygen to attenuate intermittent hypoxemia. We studied 24 patients (average age 55yrs, 29% female) with moderate-to-severe OSA (AHI4%>20/hr), treated and adherent to CPAP. Participants spent 3 separate nights in the lab under 3 counterbalanced conditions: 1) consolidated sleep with CPAP held at therapeutic pressure (CPAP); 2) CPAP withdrawn exclusively in SWS (OSASWS) breathing room air and 3) CPAP withdrawn exclusively in SWS with addition of oxygen during pressure withdrawal (OSASWS+O2). Multiple measures of sleep fragmentation (e.g., arousal index), intermittent hypoxemia (e.g., hypoxic burden), during SWS were compared according to condition. Arousal index in SWS during CPAP withdrawal was significantly greater compared to CPAP but not significantly different with and without oxygen (CPAP=1.1/hr, OSASWS+O2=10.7/hr, OSASWS =10.6/hr). However, hypoxic burden during SWS was significantly reduced with oxygen compared to without (OSASWS+O2 =23 (%min)/hr, OSASWS=37 (%min)/h). No significant OSA was observed in NREM 1, NREM 2, or REM sleep (e.g., non-SWS) in any condition. SWS-specific CPAP withdrawal induces OSA with sleep fragmentation and intermittent hypoxemia. The addition of oxygen during CPAP withdrawal results in sleep fragmentation with significantly less severe hypoxemia during the induced respiratory events in SWS. This model of SWS-specific CPAP withdrawal disrupts SWS with a physiologically relevant stimulus and facilitates the differentiation of sleep fragmentation and intermittent hypoxemia in OSA.